Unusual presentation of ruptured non coronary sinus of valsalva with new onset heart failure - Saraf, Awin; Hirachan, Anish; Sharma, Ranjit Kumar; Rajbanshi, Bijoy Gopal (Journal of Nepal Health Research Council, 2024)
Rupture of sinus of Valsalva is a rare cardiac condition which is associated with severe left to right shunting. Symptoms may include breathlessness, chest pain and fatigue or even cardiogenic shock and when untreated, this condition carries a grave prognosis. We report a case of a 57-year-old gentleman without any past comorbidities who presented to our hospital with features of acute heart failure due to rupture of sinus of Valsalva which was diagnosed by echocardiogram and further confirmed by cardiac computed tomography scan. Patient underwent successful patch closure of the defect and made a good recovery. His hospital stay was uneventful and is under regular follow up. This highlights the importance of multimodality imaging and timely treatment for cases of rupture of sinus of Valsalva. Keywords: Echocardiogram; ruptured sinus of Valsalva; sinus of Valsalva aneurysm.